Helicobacter pylori cagA/vacAs1-m1 strain is associated with high risk of fibrosis in metabolic-dysfunction-associated steatotic liver disease - Maiorana, Facundo Nicolás (2024)
Introduction and Objectives: Recent studies have suggested an association between H. pylori and metabolic dysfunction associated steatotic liver disease (MASLD). We aim to evaluate the association of H. pylori virulence genes with non-invasive markers of liver injury and fibrosis in MASLD subjects.Patients and Methods: A total of 362 dyspeptic patients who underwent gastroscopy were selected. Biochemical, clinical parameters, ultrasound, FIB-4 score, liver stiffness measurement (LSM) by vibration-controlled transient elastography (VCTE), gastric biopsies, and H. pylori virulence genes (cagA, vacA) were evaluated.Results: A cohort comprised of 61 % women and 39 % men with a median age of 52 (40−60) years. MASLD was observed in 42 %, and H. pylori-positive in 45 %. No differences were observed regarding H. pylori status at comorbid metabolic conditions. In MASLD cohort, H. pylori-positive was associated with higher AST, ALT, FIB-4 and LSM. Indeed, carriers of cagA/vacA-s1/m1-positive allelic combination were associated with higher AST, ALT, FIB-4 and LSM but not cagA/vacA-s1/m1-negative. The OR for high-risk of significant/advanced- fibrosis by VCTE (8 kPa) with H. pylori-positive was 2.56 (95 % CI, 1.2−5.75) and for cagA/vacA-s1/-m1-positive allelic carriers was 4.01 (95 % CI, 1.38−11.56), but non-significant association in cagA/vacA-s1/-m1-negative. After adjusting for age, gender, diabetes, BMI and hypertension the OR for VCTE 8 kPa with H. pylori-positive was 2.43 (95 % CI, 1.88−12.44), and cagA/vacA-s1/m1-positive allelic carriers was 4.06 (95 % CI, 1.22−14.49).Conclusions: In our cohort of FD patients with MASLD, H. pylori was associated with non-invasive markers of liver injury and fibrosis. Carriers of cagA/vacA-s1/m1-positive allelic combination showed an independent risk of significant/advanced fibrosis by VCTE.